Synthesis and antibacterial activity of Jacaranone and ester side chain analogs - Cabezas Pizarro, Jorge A. (1991)
Jacaranone and several novel ester side chain derivatives have been synthesized and tested for antibacterial activity. The syntheses of these compounds involved the convenient lithium enolate ester adition to p-benzoquinone. The results indicated an increase in the activity against Gram-positive bacteria as a consequence of increased lipophylicity in the ester side chains.